Identification Of Determinats Influencing Consumer Decision-Making For Local and Imported Fruits Purchases in Manado City - Timban, Aimar Ridel Saviola; Mandei, Juliana Ruth; Jocom, Sherly Gladys (Sam Ratulangi University, 2024)
This research aims to identify the determinants influencing consumer decision-making for local and imported fruits purchases in Manado City. The study was conducted over a period of 4 months, from June to September 2023. Primary data were collected through direct observation and interviews with respondents using a questionnaire. The data analysis used in this research is mixed-methods strategy. The sampling method utilized was accidental sampling over a 7-day period, resulting in a total of 60 respondents. The research findings indicate that the internal factor determining consumer decision-making for the purchase of local and imported fruits in the city of Manado is taste preference compatibility. Meanwhile, the external factor influencing consumer decision-making is the price and income compatibility for imported fruits and family member recommendations for local fruits. Taste preference compatibility emerges as the primary determinant in consumer decision-making for the purchase of both local and imported fruits in Manado City.